Co-formulation of the rF1V plague vaccine with depot-formulated cytokines enhances immunogenicity and efficacy to elicit protective responses against aerosol challenge in mice - Galloway, Darrell R.; Li, Jiahui; Nguyen, Nguyen X.; Falkenberg, Frank W.; Henning, Lisa; Krile, Robert; Chou, Ying-Liang; Herron, James N.; Hale, J. Scott; Williamson, E. Diane (Frontiers in Immunology, 2024)
Contribution to the field statement This manuscript describes a unique study which employed the use of depot-formulated cytokines to significantly enhance the immune response to the rF1V plague vaccine resulting in complete protection from a substantial aerosol challenge in a murine model. Our results provide additional evidence that depot-formulated cytokines offer a new approach toward vaccine enhancement. We have recently published that depot-formulated cytokines when formulated with the rF1V antigen result in significant induction of the germinal center (GC) Tfh reactions which induce long-term immunological memory to the rF1V antigen. In this study we report that the rF1V cytokine-formulated vaccine confers complete protection against aerosol challenge. Our results support and extend a series of studies which indicate the use of depot-formulated cytokines in vaccines constitute an emerging area of interest in understanding the basis of antigen presentation and the ability to induce long-term immune memory responses.